2016
DOI: 10.1055/s-0036-1584563
|View full text |Cite
|
Sign up to set email alerts
|

Chiari Type 1 Deformity in Children: Pathogenetic, Clinical, Neuroimaging, and Management Aspects

Abstract: Our understanding of cerebellar tonsillar herniation evolved over time and nowadays various pathomechanisms have been proposed. Causes of tonsillar herniation share a discrepancy between content (fore- and hindbrain) and container (supratentorial cranial vault, posterior fossa), may be associated with abnormalities of the craniocervical junction, and may have a developmental or acquired nature. In tonsillar herniation, the hindbrain is not malformed but deformed. Accordingly, "Chiari type 1 deformity," not "Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 93 publications
2
26
1
2
Order By: Relevance
“…The prevalence of CH1 was reported as 0.5%-0.9% in various populations [1,6,9,10]. In our study, we found the prevalence as 9.2% on brain MRI, much higher compared to other studies in the literature.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…The prevalence of CH1 was reported as 0.5%-0.9% in various populations [1,6,9,10]. In our study, we found the prevalence as 9.2% on brain MRI, much higher compared to other studies in the literature.…”
Section: Discussioncontrasting
confidence: 48%
“…In their study, Taştemur et al [14] stated that in individuals with tonsillar herniation, foramen magnum sagittal diameter, cerebellum height, and cerebellum sagittal diameter increases, whereas the maximum cranial height, supraocciput length, clivus length, and fossa cranii posterior height decreases. It has been stated that the cranium would bend forward and the tonsils would be lower in the case of short villus and hypoplastic condyle [6]. It was found in our study that the bone structures of the study group were smaller and foramen magnum was larger.…”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…There are other examples of malformative disorders being related to local mechanical factors, for example, arachnoid cysts with surrounding brain hypoplasia and Chiari I malformation, in which a small posterior fossa results in distortion and inferior displacement of the cerebellar tonsils, which is why the term "Chiari I deformity" was proposed instead of "malformation." 16 In patients with the ACTA2 mutation, the abnormal arterial morphology and structural brain abnormalities parallel each other in both supratentorial and infratentorial parenchymauniversally so in the anterior part of the corpus callosum, anterior cingulate gyrus, and abnormal radial frontal gyration, and variably in the brain stem. In fact, the characteristic twin peaks appearance of the pons in the axial plane seems to be related to impression by the basilar artery as well as the indentation of the lateral pontine surface that may be due to the impression by the pontine arteries coming from the basilar artery (Fig 3).…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 5 6 7 ] The onset of these symptoms, which occur in late childhood to adolescence, results in their incidental discovery upon diagnostic neuroimaging. [ 8 9 10 11 ]…”
Section: Introductionmentioning
confidence: 99%